0052 Endogenous Circadian Rhythm of Mood is Diminished in Sleep Apnea. (27th April 2018) - Emens, J; Berman, A; Butler, M; Thosar, S; Roberts, S; Clemons, N; Herzig, M; Morimoto, M; Bowles, N; McHill, A; Shea, S
Abstract: Introduction: The prevalence of mood and anxiety disorders is higher in individuals with obstructive sleep apnea (OSA). Furthermore, it is known that an endogenous circadian rhythm exists in mood and we have previously shown that both positive and negative affect contribute to this rhythm. We tested whether these rhythms were altered in individuals with untreated OSA. Methods: 21 participants were studied (aged 40–63 years; 10 females; 15 healthy controls). Control and OSA subjects were medication free and without psychiatric illness or chronic medical conditions with the exception of untreated sleep apnea (AHI≥15) in the latter, uncomplicated hypertension (BP<160/100) or obesity (BMI=28.6 ± 5.8 kg/m 2 ). Following 1–3 weeks of a regular sleep/wake schedule participants underwent a laboratory forced desynchrony protocol that distributed all scheduled sleep/wake behaviors evenly across the circadian cycle (10 scheduled, identical, recurrent 5 h 20 min 'days' in dim light). POMS-B and PANAS mood questionnaires were completed ~30 min. after each scheduled awakening. Scores were converted to z-scores and analyzed by cosinor analysis. Circadian phase at each mood assessment was determined relative to the salivary dim light melatonin onset (3 pg/ml threshold). Results: As previously reported, the POMS-B, PANAS positive affect and PANAS negative affect mood scores exhibited significant circadian rhythmicity in the control participants (all scales p ≤ 0.01). However, none of these mood assessments showed significant circadian rhythmicity in OSA participants. There was no difference in average mood scores between control and OSA subjects for any of the scales (all p> 0.10). Conclusion: The well documented endogenous circadian rhythm in mood was undetectable in these individuals with OSA. This result may be an artifact of the small number of participants with OSA, due to confounders, or the product of differences in mood rhythm amplitude or waveform in OSA. A diminished circadian rhythm in mood in OSA might contribute to the increased prevalence of mood disorders in this population (e.g., due to the loss of the circadian elevation in mood during the biological day). Support (If Any): R01-HL125893, KL2TR002370-01, F32-HL131308, UL1TR000128, and Oregon Institute of Occupational Health Sciences.